STUDY AND DESIGN OF ROOM ACOUSTICS IN RAISED BUILDING HOUSES - Sita Mulyadi, Maria
There are two types of houses – landed houses and apartment. In landed houses, different activities are done in different rooms with physical barriers. In apartment, due to its limited space, different activities can occur at the same time (multievent) in the same room with different functions (multipurpose). Therefore, noise sources need to be localized for one activity to not interfere with other activities happening at the same time. The first step of this study is to understand the acoustic characteristics of the apartment. The study is conducted by evaluating noise level in several receiver points using CATT Acoustic. Study shows that acoustic comfort is not yet obtained in apartment with multievent and multipurpose characteristics, shown by noise criteria that exceed the standard for apartment. The next step is to apply acoustic quality treatment for noise source and noise path. The result shows that switching sound sources into lower noise is the most impactful treatment. This is proven by the attenuation in noise loudness, which occur within 14 – 35 dB range, and the decrease in Noise Criteria within 14 – 35 range, whereas acoustic treatment by changing the material and layout decrease noise loudness by 3 – 5 dB and Noise Criteria by 0 – 9.